Persistence of infectious hepadnavirus in offspring born to mothers convalescent from hepatitis in the woodchuck model of hepatitis B - Coffin, Carla S., 1971- (St. John's, NF : [s.n.], 1997)
Thesis (M.Sc.)--Memorial University of Newfoundland, Faculty of Medicine, 1997. Medicine Bibliography: leaves 189-204. ABSTRACT Hepatitis B virus (HBV) is primarily an hepatotropic vims, although evidence of viral infection in lymphoid cells has also been observed. The virus induces life-threatening liver diseases, such as cirrhosis and hepatocellular carcinoma and is a major public health problem with more than 300 million chronically infected people worldwide. It is also evident that transmission of HBV from infected mothers to their babies is the most important mechanism by which the virus is maintained within the population. Recent findings have established the existence of a serologically undetectable persistent carrier state of HBV in apparently completely healthy individuals convalescent from an acute episode of hepatitis B. In these individuals, traces of HBV genomes were documented in serum and circulating lymphoid cells years after recovery. Related findings of the life-long hepadnaviral persistence after a transient exposure to woodchuck hepatitis virus (WHV) has been demonstrated in this laboratory in a woodchuck model of hepatitis B. -- The current study was undertaken to learn about the risk of hepadnavirus transmission to newborn woodchucks from mothers with complete serological recovery from experimentally induced viral hepatitis and about natural course and molecular features of virus persistence in these offspring. The specific aims of this investigation were: (1) to determine whether hepadnaviral genomes can be transmitted from maternal woodchucks with a past episode of acute WHV hepatitis to their offspring; (2) if in fact this vertical transmission occurs, to identify reservoirs of hepadnavirus replication during long-term follow-up of these newborn animals; (3) to characterize physicochemical properties of molecules carrying WHV DNA in sera of these offspring; (4) to test whether silent carriage of WHV genomes acquired after vertical transmission reflects the existence of biologically competent virus infectious to WHV-naive woodchucks, and (5) to determine whether the offspring carrying WHV traces are susceptible to WHV infection. In this work, 11 offspring born to 4 woodchuck mothers convalescent from an acute episode of viral hepatitis were investigated. -- Our results have shown that serologically silent WHV carriage acquired after a self-limited episode of viral hepatitis is transmittable from mothers to newborns as an asymptomatic chronic infection. Importantly, all of the offspring tested carried WHV DNA through the entire follow-up, lasting for more then 3 years after birth, and remained nonreactive for immunovirological markers of WHV infection unless challenged with WHV. WHV DNA and RNA specific sequences were detectable both in the liver and lymphoid cells in the majority of the animals, although in some offspring WHV persisted exclusively at a extrahepatic location in the lymphatic system. Particles carrying WHV DNA in sera of offspring with WHV genomes in both the liver and lymphoid cells or the lymphatic system alone had physicochemical properties comparable to those of complete WHV virions. In addition, virus contained in offspring sera with or without WHV DNA expression in the liver as well as, culture supernatant from mitogen-stimulated peripheral blood mononuclear cells were infectious to WHV-naive woodchucks. Finally, despite silent carriage of WHV traces, the offspring were susceptible to WHV challenge. Since there are significant pathobiological similarities between HBV and WHV, it is possible that a comparable situation may exist in babies born from mothers with a past history of hepatitis B.